The Career Development of Young Japanese People: The Attainment of Self-Confidence in Career Development - Chisato Ogawa (European Regional Science Association (ERSA), 2006)
Many young Japanese people seem to be able to determine goals towards their career development. However, many appear to struggle to take action towards their intended goal, often due to a lack of confidence, or an inability to make decisions without guidance or assistance from others. As a result, we think that perhaps a misconception is formulated by the community that young Japanese people drift around aimlessly without a sense of purpose or direction towards a career path, even after graduating from universities. In contrast, students in professional training schools appear to be more self-confident and decisive in choosing their career path. Perhaps, this is due to the different educational environments between the professional training schools and the general school system in Japan. For example, students who attend professional training schools live together during the training, whereby they have the opportunity to interact with each other under the guidance of their teachers. As a result, students appear to develop effective communication skills that perhaps contribute to increased self-confidence. This research focuses on the career development of young Japanese people to analyze how they attain self-confidence to action their career development path. Semi-structured interviews were conducted with young Japanese people including university students and professional candidates to examine their ability to identify a career path. We believe that young Japanese people are able to identify their career path and the steps necessary to follow, however it appears that many lack the confidence to initiate the process towards their chosen career.
Keywords: 330